Time of artificial insemination and pregnancy rates in Boran (Bos indicus) cattle - Mukasa-Mugerwa, E.; Tegegne, Azage; Warnick, A.C. (1989)
Results of a study conducted to determine the conception rates of Boran cattle following artificial insemination of different times from the onset of induced oestrus compared with artificial insemination following natural oestrus.